Marine medicinal glycomics - Pomin, Vitor H. (Frontiers in Cellular and Infection Microbiology, 2014)
Glycomics is an international initiative aimed to understand the structure and function of the glycans from a given type of cell, tissue, organism, kingdom or even environment, as found under certain conditions. Glycomics is one of the latest areas of intense biological research. Glycans of marine sources are unique in terms of structure and function. They differ considerably from those of terrestrial origin. This review discusses the most known marine glycans of potential therapeutic properties. They are chitin, chitosan, and sulfated polysaccharides named glycosaminoglycans, sulfated fucans and sulfated galactans. Their medical actions are very broad. When certain structural requirements are found, these glycans can exhibit beneficial effects in inflammation, coagulation, thrombosis, cancer growth/metastasis and vascular biology. Both structure and therapeutic mechanisms of action of these marine glycans are discussed here in straight context with the current glycomic age through a project suggestively named Marine Medicinal Glycomics.